Penerapan Terapi Individu Bercakap Cakap Pada Pasien Halusinasi Pendengaran - Reski Ramdani; Basmalah Basmalah; Rusli Abdullah; Ekayanti H. Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Hallucinations are symptoms of mental disorders in which the patient experiences sensory changes in perception, feels false sensations in the form of sound, sight, taste, touching or shaming, the client feels a stimulus that does not exist. Objective: Knowing the application of individual therapy to auditory hallucination patients. Method: Quality research using the descriptive method of case study research. Results: Shows that with individual therapy, the patient can distract the patient so that he can control the hallucinations he experiences. Conclusion: That individual therapy in auditory hallucination patients can effectively control hallucinations. Recommendations should consider creating a new policy for nurses, particularly room nurses, to perform continuously to reduce the frequency of people with mental health conditions